Successful treatment of allergic bronchopulmonary aspergillosis using a combination of oral voriconazole and the bronchoscopic instillation of amphotericin B - HuaMan Wu; MaoLiang Tian; Zhao Chen; XiaoYu He; Yang Zeng; Lun Wang; ZhiPing Deng (Medicine, 2026)
Rationale: Allergic bronchopulmonary aspergillosis (ABPA) is a complex pulmonary disease that results from hypersensitivity reactions triggered in response to A fumigatus . To date, there have been few reports of ABPA patients exhibiting elevated serum carcinoembryonic antigen levels. Moreover, while systemic antifungal treatment often results in substantial side effects when administered to ABPA patients, there has been little published regarding bronchoscopic amphotericin B instillation as an alternative treatment strategy. Patient concerns: We describe an ABPA patient who was repeatedly misdiagnosed with lung cancer. This 60-year-old woman complained of a 5-year history of a recurrent cough with whitish viscous sputum that had recurred and worsened within the 2 days before presentation. This woman had visited hospitals many times during this interval, and pulmonary computed tomography scans had revealed an occupying lesion in the left upper lobe of her lung. This, coupled with her elevated serum carcinoembryonic antigen levels and other lung cancer markers, led to the misdiagnosis of lung cancer. Diagnoses: As we found that she also exhibited elevated serum IgE and circulating eosinophil counts, and Aspergillus was detected through rapid on-site evaluation, we sent a further blood sample for fungal antigen-specific antibody testing. This approach revealed markedly elevated levels of A fumigatus -specific IgE, Aspergillus -specific IgG and IgM, leading to the confirmation of an ABPA diagnosis. Interventions: The patient was administered inhaled budesonide together with antifungal therapy consisting of oral voriconazole and bronchoscopic amphotericin B instillation. She was additionally provided empiric antibiotic treatment to alleviate her cough and reduce phlegm production. Outcomes: Her symptoms and the associated lung lesion improved significantly. Lessons: Bronchoscopic amphotericin B instillation represents a safe and effective approach to treating ABPA, providing a means of increasing local drug concentrations while minimizing the potential for systemic adverse reactions.